PENINGKATAN KEMAMPUAN BIOENTREPRENEURSHIP KELOMPOK TANI MELALUI PELATIHAN BONJIKA (ABON BIJI NANGKA) - Aden Arif Gaffar Aden; Muhamad Kurnia Sugandi Andi; Iim Halimatul Mu'minah Iim; Yeni Suryaningsih Yeni; Sindi Sugiharti Sindi (Universitas Majalengka, 2022)
The potential in Cikedung Village, Indramayu Regency has several advantages in the delivery of the agricultural and fruit plantation sectors and the low utilization of jackfruit and jackfruit seeds in the food sector is only about 10% due to the lack of public interest in processing jackfruit seeds. This jackfruit seed shredded product